Demonstration by Efficient Cause on Aristotle’s De generatione et corruptione 2. 10 (Circe de clásicos y modernos, 2018)
We take as an object of study the text De generatione et corruptione (GC) 2. 10 to establish the use of scientific demonstration. Aristotle states in GC 1 the principles of generation but then he builds genuine scientific demonstrations basing precisely on those principles. We will reconstruct a specific passage of GC 2. 10 in order to defend the hypothesis of the real use of scientific demonstration in scientific treatises. Particularly, in the frame of the four Aristotelian causes, we show that this demonstration makes explicit the efficient cause of the phainomena of generation and corruption.
Keywords: Aristotle; De generatione et corruptione; scientific demonstration; efficient cause